2018
DOI: 10.30552/ejep.v10i1.130
|View full text |Cite
|
Sign up to set email alerts
|

Mapas conceptuales y simulaciones en un sistema informático para la enseñanza de la Psicología

Abstract: PSICO-A es un sistema informático para el aprendizaje de la Psicología. Está especialmente destinado a estudiantes de Educación Secundaria. Es el primer sistema integrado computacional concebido para la enseñanza de unidades didácticas de Psicología. PSICO-A combina diversas herramientas e influencias didácticas: introduce mapas conceptuales, recuperación libre del recuerdo, un mecanismo efectivo de “feedback”, simulaciones, juegos digitales y explora la capacidad metacognitiva de los alumnos. Hemos confirmado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Leading trends in managing the development of modern pedagogical universities, conducting an audit of the organization of the educational process, introducing active and interactive forms of classes, introducing all the latest information technologies into the educational process, in fact, only deepen these trends. It is difficult to overestimate their role here, since universities themselves create the latest educational technologies, test them, saturate them with content and transfer them for use at earlier stages of education [10]. As an example, we can give not only practical or laboratory works in virtual reality, but also lectures held in leading university centers, when the entire group, led by a teacher-guide, visit various virtual industries, institutions, and organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Leading trends in managing the development of modern pedagogical universities, conducting an audit of the organization of the educational process, introducing active and interactive forms of classes, introducing all the latest information technologies into the educational process, in fact, only deepen these trends. It is difficult to overestimate their role here, since universities themselves create the latest educational technologies, test them, saturate them with content and transfer them for use at earlier stages of education [10]. As an example, we can give not only practical or laboratory works in virtual reality, but also lectures held in leading university centers, when the entire group, led by a teacher-guide, visit various virtual industries, institutions, and organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of foreign psychological and pedagogical sources showed that students in the learning process need to: -to master social skills, to understand the values and lifestyle associated with this profession. [15][16][17][18][19], -to be able to manage conflict situations (С.А.Parker, К Bickmore) [20], -to master the physiological foundations for understanding, studying and justifying somatophysiological changes in the body (L. Sanci) [21], -to have pedagogical training that allows future specialists to properly organize psychological and educational support for children (C.G. Alemán, A.P.…”
Section: Introductionmentioning
confidence: 99%